Design‐Driven Innovation in Retailing: An Empirical Examination of New Services in Car Dealership. (29th July 2016) - Bellini, Emilio; Dell'Era, Claudio; Frattini, Federico; Verganti, Roberto
Abstract : The paper focuses on innovation in the automotive retail industry. Innovation in service has been acknowledged as a critical source of competitive advantage and retail firms are looking for innovations that can increase their competitiveness. This notwithstanding, there are no studies that focus on whether and how design‐driven innovation (DDI) can be pursued by retail firms as an innovation strategy. In the attempt to close this gap in our understanding of innovation in retail firms, this paper discusses 104 examples of strategic innovation projects identified by automotive retail firms which operate in the UK, Germany, Italy, Serbia and Spain. The exploratory empirical analysis shows that a certain number of automotive retail firms (although not the majority) choose DDI as a strategy embodied in strategic innovation projects designed to achieve superior performance. Moreover, by following the typology proposed by Sawhney and colleagues, the analysis suggests that these projects are elicited by spatial reconfiguration and expansion, whereas temporal innovation does not seem to provide a fertile ground for DDI.